2020
DOI: 10.3892/or.2020.7644
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of TGF‑β‑SMAD‑mediated epithelial‑mesenchymal transition in pro‑metastatic property of PAX6

Abstract: Paired box 6 (PAX6) is a transcription factor that has oncogenic features. In breast cancer, PAX6 facilitates tumor progression; however, the underlying mechanism is largely unknown. The majority of breast cancer-related mortalities are associated with metastasis of cancer cells. Therefore, the present study aimed to investigate the role of PAX6 in breast tumor metastasis. PAX6 was stably overexpressed in breast cancer cells to perform tumor migration and metastasis assays in vitro and in vivo. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Our transcriptomic analysis (Fig. 8 B) identified another factor regulated by TGF-beta signaling, and essential for eye formation, namely pax6 46 . The zebrafish genome houses two Pax6 genes, among which only Pax6a plays a role in the ocular tissues, while Pax6b is mainly found in the pancreas 47 .…”
Section: Resultsmentioning
confidence: 94%
“…Our transcriptomic analysis (Fig. 8 B) identified another factor regulated by TGF-beta signaling, and essential for eye formation, namely pax6 46 . The zebrafish genome houses two Pax6 genes, among which only Pax6a plays a role in the ocular tissues, while Pax6b is mainly found in the pancreas 47 .…”
Section: Resultsmentioning
confidence: 94%
“…Platelets enhance tumor metastasis by expressing immunoregulatory proteins, such as the glucocorticoid induced TNF-related protein to protect tumor cells from the innate immune system [39,40]. Furthermore, A recent study demonstrated that the interactions between platelets and tumor cells facilitated metastasis by promoting epithelial mesenchymal transition through the TGFB/SMAD and NFKB pathways.They also found that inhibition of these two pathways solely could suppress metastasis in vivo [41].…”
Section: Discussionmentioning
confidence: 95%
“…PAX6 belongs to the PAX family and is a vital transcription factor in a variety of biological processes [ 42 ]. Other investigations have also supported PAX6 as an oncogene and have characterized its overexpression across numerous types of human cancers [ 43 , 44 ]. Moreover, its cancer-promoting effects can be regulated by miRNAs [ 43 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%